A link between NMDA receptor hypofunction and GABAergic inhibition in the modulation of cognition: a comparison of neural and cognitive changes in rat models of NMDA receptor hypofunction and of prefrontal and hippocampal neural disinhibition - Taylor, Charlotte (2024)
NMDA receptor (NMDAR) hypofunction and impaired GABAergic inhibition, so-called neural disinhibition, in the hippocampus and prefrontal cortex, have both been implicated in the pathophysiology of schizophrenia. Moreover, it has been suggested that NMDAR hypofunction and neural disinhibition are mechanistically linked and may converge on a common pathological hub. NMDAR hypofunction in rodents has been reported to mimic certain aspects of cognitive deficits associated with schizophrenia, alongside pathological reductions in hippocampal and prefrontal GABAergic markers. Given the importance of GABAergic inhibition in the hippocampus and prefrontal cortex for a range of cognitive functions, hippocampal and prefrontal neural disinhibition may underlie some of the cognitive deficits found in rodent models of NMDAR hypofunction. Here, we examined the overarching hypothesis that NMDAR hypofunction impairs cognition by causing neural disinhibition in the hippocampus and prefrontal cortex. In chapter 1, we reviewed the current evidence for this hypothesis, which demonstrated a compelling case for neural disinhibition in acute and neurodevelopmental models of NMDAR hypofunction. However, importantly, studies investigating the impact of sub-chronic NMDAR hypofunction on GABAergic function were equivocal in support of the hypothesis, and the role of these processes in mediating cognition on the watermaze delayed-matching-to-place (DMP) and novel object recognition (NOR) task, respectively, had not been investigated. In subsequent chapters, we aimed to address the hypothesis experimentally, by comparing and examining the cognitive and neural changes in rat models of sub-chronic NMDAR hypofunction and regional neural disinhibition.